Understanding corporate moral development in the context of rapid and radical changes : the case of Estonia - Kooskora, Mari (2008)
This dissertation focuses on business ethics by researching the phenomenon of corporate moral development (CMD) within the context of a society experiencing rapid and radical change - Estonia. The study consists of two parts: an introductory essay and five articles. The introductory essay explains the key topics, outlines how the articles relate and highlights the theoretical and practical contribution that this dissertation represents. The research argues that social phenomena are context-dependent and should be studied and understood as such. Consequently, the research adopts the idea that it is important to consider the wider societal context and history in order to understand CMD in businesses organizations. The model by Reidenbach and Robin (1991) is used, considering the societal context in which a business organization operates. In particular, the following research question is answered: How can different stages of CMD be described and conceptualized when contextual influences on the Estonian business community during radical political, economic and social changes are taken into consideration? The phenomenon is studied from three different angles - corporate governance, corporate social responsibility and ethical leadership - and in terms of how it can be enhanced through teaching. The dissertation applies both descriptive and normative knowledge, and makes three main contributions to prior literature, firstly by providing a holistic and rich description of the phenomenon from the viewpoint of the development of Estonian society during 1985-2005; secondly by investigating it from the contextual perspective, with particular attention paid to political, economic and social environments and thirdly by offering a practical contribution to present-day Estonian organizations and their managers. As a result of this study the conceptual model of CMD was re-conceptualized by adding two lower stages that describe and conceptualize the impact of transformation in society. The results show that there has been clear progress in CMD in the Estonian business community. The results suggest that the changes are caused by external sources, while internal forces had less impact. Therefore the model of CMD needs to be completed so that the triggers do not always have to come from within business organizations, but also from external forces. Further the research showed that in order to strengthen CMD in Estonian business life, particular attention should be directed at developing and implementing societal norms as a basis for sustainability in business and teaching business ethics and corporate social responsibility as a priority in business schools. In general it can be said, that the 'modern' business environment in Estonia is relatively young and companies are still coming to understand new methods and new paradigms such as corporate moral development.